VOC measurements during OASIS Barrow field intensive Spring 2009 (Arctic Data Center, 2016)
A measurement intensive campaign was carried out in Barrow, Alaska in spring 2009 as part of the Ocean-Atmosphere-Sea-Ice-Snowpack program. This dataset contains Volatile Organic Compounds (VOCs) measured using the Trace Organic Gas Analyzer (TOGA) during the campaign.